Impact of Harmonics on Power Quality and Losses in Power Distribution Systems - M. Jawad Ghorbani; Hossein Mokhtari (Institute of Advanced Engineering and Science, 2015)
This paper investigates the harmonic distortion and losses in power distribution systems due to the dramatic increase of nonlinear loads. This paper tries to determine the amount of the harmonics generated by nonlinear loads in residential, commercial and office loads in distribution feeders and estimates the energy losses due to these harmonics. Norton equivalent modeling technique has been used to model the nonlinear loads. The presented harmonic Norton equivalent models of the end user appliances are accurately obtained based on the experimental data taken from the laboratory measurements. A 20 kV/400V distribution feeder is simulated to analyze the impact of nonlinear loads on feeder harmonic distortion level and losses. The model follows a “bottom-up” approach, starting from end users appliances Norton equivalent model and then modeling residential, commercial and office loads. Two new indices are introduced by the authors to quantize the effect of each nonlinear appliance on the power quality of a distribution feeder and loads are ranked based on these new defined indices. The simulation results show that harmonic distortion in distribution systems can increase power losses up to 20%.